The Use of Wordwall Media in Learning Assessment to Capture the Meaning of Poetry Texts - Adlin; Supriyadi; Muslimin (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the design, use, and evaluate the use of the Wordwall application in assessing poetry text learning among 11th grade students at Madrasah Aliyah Sabrun Jamil Botupingge in the 2024/2025 academic year. This research was conducted at Madrasah Aliyah Sabrun Jamil Botupingge in 2025. The number of informants in this study involved 10 students. This study used a qualitative descriptive method and qualitative research type to provide an in-depth description of the phenomenon being studied. Data sources were obtained from teaching modules or the Wordwall digital application design, the learning process, and students. Data collection techniques were carried out through documentation, observation, and Wordwall application tests. Data analysis techniques were carried out through four main stages, namely data reduction to focus information, narrative data presentation, in-depth data analysis, and conclusion drawing and verification to produce accurate findings. The results showed that the Wordwall application design was systematically constructed through the integration of pedagogical, technical, and visual aspects in line with the curriculum and poetry-building indicators. Implementation in the field through the Wooden Desk-themed digital quiz feature proved to be interactive and adaptive, capable of transforming conventional assessments into a dynamic digital experience. The use of gamification features such as leaderboards and timers significantly increased students' motivation, confidence, and active participation during the assessment process. The evaluation results confirm that Wordwall is a practical and accurate assessment tool for measuring literary competence. Overall, this application is effective as a continuous assessment model that is responsive to the technological needs and characteristics of students in the digital age.